Research progress on degradative solvent extraction of low-rank coals - Zhu GUO; Xian LI; Zhiyu LI; Zhenzhong HU; Mei ZHONG; Chunliang ZHAO; Ciliang XIA; Guangqian LUO; Shulin WANG; Hong YAO (Meitan kexue jishu, 2023)
The degradative solvent extraction of low rank coal is the use of solvents to extract low rank coal under mild conditions, through the dehydration and multi-stage separation of the raw coal： the extraction products with no water content, no ash content, high calorific value properties and excellent thermoplastic properties， and low moisture of the extractive residual coal can be obtained. At the same time, the products have practical application advantages in many fields such as coal coking, advanced fuel and carbon material preparation, which have high added value, and the solvent in this technology has the advantage of being recyclable. Therefore, degradative solvent extraction is one of the effective ways to realize the graded fractionated conversion and utilization of low-rank coal. This review firstly introduces the existing low rank coal upgrading methods, and then reviews the development of degradative solvent extraction, focusing on the various influencing factors, reaction mechanisms, existing processes and product utilization of low rank coal upgrading by degradative solvent extraction. Finally, using the "Web of Science core collection" as the data source, the knowledge graph of coal solvent extraction was carved using CiteSpace scientometric software, and the research themes were analyzed to summarize the research directions and predict the research hotspots, providing some reference value for the research of degradative solution extraction of low-rank coal. The comprehensive analysis shows that: the selection of new low-cost green solvents, structural characterization and high-value utilization of extraction products have high research trends, while in-depth research on extraction mechanism and targeted regulation of extractant properties is needed to further promote the process of large-scale production.